2018
DOI: 10.1002/admi.201701065
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Biomolecular Crystallization on Amyloid‐Like Superhydrophobic Biointerface

Abstract: biohybrids. [6] With respect to the crystallization, a protein-based biopolymer substrate is typically utilized in nature to develop excellent biomineralization system. [7] Vice versa, the utilization of mineral substrates, [8] chemically modified mica, [9] gel, [10] silanized polystyrene wells, [11] lipid layers, [12] polymeric film surfaces [13] as well as porous media, [14] etc. have contributed a lot to protein crystallization. Some conjectures have been made from these studies, typically including concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…As a heterogeneous nucleation platform, superhydrophobic surfaces have demonstrated values in facilitating the biocrystallization process and endowing the products with high quality. [172,173] Especially the biomolecule-assembled superhydrophobic surfaces have intrinsic advantages of biocompatibility, nontoxicity, and biodegradability, which make them suitable for biomedical applications. Based on the self-assembly of lysozyme, Gao et al fabricated a superhydrophobic surface and applied it for protein crystallization.…”
Section: Biocrystallizationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a heterogeneous nucleation platform, superhydrophobic surfaces have demonstrated values in facilitating the biocrystallization process and endowing the products with high quality. [172,173] Especially the biomolecule-assembled superhydrophobic surfaces have intrinsic advantages of biocompatibility, nontoxicity, and biodegradability, which make them suitable for biomedical applications. Based on the self-assembly of lysozyme, Gao et al fabricated a superhydrophobic surface and applied it for protein crystallization.…”
Section: Biocrystallizationmentioning
confidence: 99%
“…Wu et al also took advantage of a superhydrophobic proteinaceous platform to facilitate preferential crystallization of proteins and peptides. [173] These typical examples reveal that surfaces with special wettability would open a new chapter in fundamental research of biomolecules.…”
Section: Biocrystallizationmentioning
confidence: 99%
“…It has been reported that an intramolecular disulfide bond is critical to stabilize protein tertiary or quaternary structures. , As a result, a reduction in the number of disulfide bonds led to a mild unfolding of the proteins, which subsequently induced the transformation of chain secondary structures into predominant β-sheets in insulin single crystals . In this regard, Yang et al developed a strategy to realize the nucleation–crystallization of proteins by unfolding native lysozyme, insulin, bovine serum albumin (BSA), or α-lactalbumin via the reduction of their intramolecular disulfide bonds. Tris­(2-carboxyethyl)­phosphine (TCEP) reduced disulfide bonds effectively in lysozyme, , which consequently induced protein unfolding and then self-assembly of unfolded protein chains into short-range β-sheets without complex pre-steps (Figure A). The reduction of disulfide bonds was clearly reflected through Raman spectra and N -(1-pyrenyl)­maleimide (NPM) assay (Figure B), and the transformation to β-sheets was then characterized by circular dichroism (CD) and Fourier transform infrared (FTIR) spectroscopy (Figure C).…”
Section: Nucleation Through Assembly Of Molecular Secondary Structuresmentioning
confidence: 99%
“…The unfolded protein aggregates containing short-range interchain alignments were sensitive to the solvent environment, so the structures of such short-range β-sheet assemblies could be tuned by using different conditions. , Under quasi-equilibrium conditions, short-range β-sheets could be further crystallized to form vast protein nanocrystals (Figure F). These nanocrystals had typical “core–shell” structures, in which crystalline cores, orderly packed from β-sheets, were embedded into amorphous flexible chain shells, similar to the structure of organic–inorganic nanocrystals in biomineralization, and could assemble with a specific orientation into mesocrystals (vide infra).…”
Section: Nucleation Through Assembly Of Molecular Secondary Structuresmentioning
confidence: 99%
See 1 more Smart Citation